2020
DOI: 10.1088/2058-6272/ab7b0e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E × B flow shear stabilization on particle confinement and density peaking at JET

Abstract: The impact of the É B flow shear stabilization on particle transport and density peaking at JET is analyzed in the framework of integrated modelling with the CRONOS code. For that purpose, plasmas from a power scan which show a significant increasing of density peaking with the injected neutral beam injection power have been used as a modeling basis. By means of simulations with the quasilinear model GLF23 for the heat and particle transport, a strong link between the particle confinement and É B flow shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The fraction ⟨| ⃗ ∇ρ t |⟩/⟨| ⃗ ∇ρ t | 2 ⟩ varies between 0.83 and 0.92 for JET and 0.69 and 0.87 for DIII-D and the fraction ⟨| ⃗ ∇ρ t |⟩ 2 /⟨| ⃗ ∇ρ t | 2 ⟩ varies between 0.93 and 0.97 for JET and 0.85 and 0.95 for DIII-D. These values are true between ρ t = 0.5 and 0.8 The first term on the RHS is the peaking that comes from the turbulent transport, the same term as displayed in equation (17). This term is entirely determined by the ratio of the particle balance pinch and diffusion.…”
Section: Particle Balance Diffusion and Pinchmentioning
confidence: 82%
See 1 more Smart Citation
“…The fraction ⟨| ⃗ ∇ρ t |⟩/⟨| ⃗ ∇ρ t | 2 ⟩ varies between 0.83 and 0.92 for JET and 0.69 and 0.87 for DIII-D and the fraction ⟨| ⃗ ∇ρ t |⟩ 2 /⟨| ⃗ ∇ρ t | 2 ⟩ varies between 0.93 and 0.97 for JET and 0.85 and 0.95 for DIII-D. These values are true between ρ t = 0.5 and 0.8 The first term on the RHS is the peaking that comes from the turbulent transport, the same term as displayed in equation (17). This term is entirely determined by the ratio of the particle balance pinch and diffusion.…”
Section: Particle Balance Diffusion and Pinchmentioning
confidence: 82%
“…It adds rotation to the plasma which changes the E × B shear which affects the turbulent transport [14,15]. It has been shown that this increase in E × B shear adds to the inward pinch [16,17]. The NBI also creates a locally higher current which changes the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The 𝐸 × 𝐵 flows play a central role in regulating the saturation level of the turbulence and turbulent transport. [15] The 𝐸 × 𝐵 velocity shear caused the reduction in turbulence and transport. [16] On the other hand, the flow shear may also make a destabilizing contribution as well.…”
Section: Introductionmentioning
confidence: 99%
“…The related codes have been widely developed to study the properties of ITG and TEM [3] turbulence. In addition, transport behavior in the experiments is analyzed [4]. Direct numerical simulations have successfully provided tremendous insight into the underlying transport physics, and they are currently a powerful tool in transport study.…”
Section: Introductionmentioning
confidence: 99%